Transformasi Transformasi Presensi Manual ke Digital dalam Upaya Peningkatan untuk Kualitas Dokumentasi Pembelajaran - Muhammad Adzar Al Yaman; Muhammad Taufiq; Sulidar Fitri; Umar Al Faruq (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Digital transformation in the world of education is a strategic step to improve efficiency and quality of services, including in terms of attendance recording. This study aims to examine the change in the manual attendance system to digital in an effort to improve the quality of learning documentation at PPTQ Al Huda. The method used is a descriptive qualitative approach with data collection techniques through distributing questionnaires to teachers and academic staff. The results of the study indicate that the implementation of digital attendance has been significantly beneficial for the majority of respondents. This system is considered more practical, accurate, and efficient than manual methods. Digital attendance not only makes it easier to record student attendance, but also strengthens transparency, accountability, and supports data-based decision making. In addition, this system plays a role in improving student discipline and responsibility. Digital attendance has also been proven to reduce the practice of asking for attendance, minimize recording errors, and facilitate real-time data access by Islamic boarding school administrators. Ease of use and convenience of the system are also supporting factors for successful implementation. Moreover, the adoption of digital attendance encourages the development of a technology-based culture within the institution. It fosters digital literacy among educators and students, enhancing their adaptability to technology in daily academic routines. This transformation aligns with the broader educational goal of integrating technology to create a modern, effective, and sustainable learning environment. Therefore, the shift to a digital attendance system is not only a technical innovation but also a reflection of institutional commitment to continuous improvement and educational excellence. This innovation proves to be a relevant and strategic solution for strengthening educational administration in Islamic boarding schools.